Gerakan Hak-Hak Disabilitas di Bali: Analisis Fenomenologi dalam Penyebaran Norma Internasional Hak-Hak Disabilitas - Wiranata, I Made Anom (Andalas Journal of International Studies (AJIS), 2022)
The Convention on the Rights of Persons with Disabilities (CRPD) ratified by Indonesia in 2011, presents the perspective of the fulfillment of the rights of persons with disabilities. The process of internalizing disability rights norms at the domestic level does not occur linearly, but through the struggles of  the disability rights activists in their respective regions. Taking place in Bali, this study investigates the motivations and causes of the involvement of disability rights actors in disseminating disability rights norms. By using a transnationalism theory and phenomenological methods, this study finds that the spread of international norms on disability rights in Bali occurred as a social movement that had grown before the ratification of the CRPD. There is an open interaction between local, national and international actors. The self-struggle against discrimination and the interaction of movement actors in Bali with international volunteers who have a cosmopolitan consciousness, gave birth to the movement agency. CRPD provides an opportunity and direction for movement actors to advocate local regulations for the fulfillment of disability rights. In their social environment, they build awareness to the persons with disabilities and their families, as well as showed the wider community that persons with disabilities have the competence to be independent.